Japanese Mothers’ Communication on Sexuality Education with Elementary School-Age Children (7–11) - Takahiro Sato; Chie Kataoka; Tomomi Mitsutake; Cathy McKay; Hirotaka Kizuka; Manami Koide; Miho Miyachi; Takafumi Tomura; Yu Furuta (SAGE Open)
The purpose of this study was to explain Japanese mothers’ communication on sexuality education with elementary school-age children (7–11). There were six mothers who consented to participate in this study, sharing their thoughts, opinions, and experiences related to sexuality education. A constant comparative analysis method was used to analyze the data, with three themes emerging from the data: (a) teaching the importance of self-protective behaviors , (b) finding the right timing to have important conversations regarding sexuality , and (c) understanding the balance of what to cover at school versus what to cover at home. To advance the quality of parent and family communication regarding sexuality education, teachers and administrators need clear and focused goals related to the applicability and caliber of sexuality education programs and curricula at elementary schools.